Pengaruh Promosi dan Kualitas Produk Terhadap Loyalitas Pelanggan di Shopee - Salsabila Nur Azizah; Natal Indra (Master Manajemen, 2024)
The purpose of this study was to determine how much influence promotion and product quality have on loyalty at Shopee. The research method used is a quantitative method approach with data collection techniques using purposive sampling with a population of 100 and samples taken using the slovin formula, namely 50 respondents. Data collection using SPSS 25 for instrument testing, multiple regression analysis, hypothesis testing. Based on the results of partial hypothesis testing, it shows that the promotion variable has a significant value of 0.001 T table, namely 1.678, which means that it has a significant value and the T table value has an effect on customer loyalty. And the product quality variable has a significant effect on customer loyalty. Simultaneously, promotion and product quality have a significant effect on customer loyalty. The most dominant variable influencing is product quality.